Salvage of Intraoperative Rupture of a Wide-Necked Middle Cerebral Artery Bifurcation Aneurysm: The Felt-Fenestrated Clipping Technique. Issue 2 (2nd February 2023) - Housley, Steven B.; Monteiro, Andre; Cappuzzo, Justin M.; Khawar, Wasiq I.; Levy, Elad I.
Abstract : BACKGROUND: Intraoperative aneurysm rupture during microsurgical clipping can be managed with different salvage techniques. In an aneurysm with a very wide neck that is located at a bifurcation, repairing an iatrogenic tear can be challenging and carry the risk of branch occlusion and infarction. OBJECTIVE: To describe a variation of the cotton-clipping technique modified to better fit the bifurcation anatomy, which we call "felt-fenestrated clipping." METHODS: An illustrative case of intraoperative rupture of a wide-necked middle cerebral artery bifurcation aneurysm is presented. Radiological imaging, operative video, and technique illustration were obtained and prepared for this report. RESULTS: A middle-aged woman underwent microsurgical clipping of a wide-necked middle cerebral artery bifurcation aneurysm. A right-angle clip became dislodged from the clip applier and snapped across the aneurysm causing a small rupture at the base. This was later determined to be the result of improper placement of a standard clip onto a mini-clip applier. After a few salvage attempts, a small piece of Teflon felt was placed over the rupture site and held in place using a straight, fenestrated clip. Then, the right-angle clip was applied over the true neck of the aneurysm and the edge of the rupture site, covering the Teflon felt to obtain true hemostasis. CONCLUSION: We demonstrate a technically successful felt-fenestrated clipping technique for treatment of an intraoperative rupture not amenable to other salvage options. This technique is useful to achieve hemostasis while preserving branches in wide-necked bifurcation aneurysms.